To Manage or To Comprehend: Methodological Issues of Social Space Analysis in Urban Studies - Šarūnas, Tadas (Sociologija. Mintis ir veiksmas, 2024)
Contemporary interdisciplinary urban studies often rely on census data. While analyses based on such data provide insights into territorial and spatial processes, they also present clear epistemological limitations. Generated by the administrative apparatus of the state, these data offer pre-constructed representations of social reality, primarily intended for governance purposes. Consequently, researchers using such data risk accepting them as objective reality. This paper explores how the use of geo-referenced data, particularly its mapping, affects the researcher’s imagination. Drawing on Pierre Bourdieu’s critique of classification, the paper proposes viewing census categories as individual descriptors of a multidimensional social space. Using the case study of the relationship between social and physical space in the city of Stavanger, it discusses possible methodological alternatives for the analysis of geo-referenced census data. In Lithuania, spatial research remains largely dominated by positivist approaches. Moving beyond this paradigm could allow for better use of emerging open data infrastructures and foster a deeper understanding of Lithuanian social structures and their influence on spatial change.
Keywords: social space; physical space; geo-referential data